Analysis of Volatile Flavour Compounds in Unloosed and Loosed Tobaccos - Zhong, Hongxiang; Cai, Jibao; Yang, Jun; Yang, Dahui; Fan, Jianqiang; Xie, Wei; Su, Qingde (Asian Journal of Chemistry, 2016)
The volatile flavour compounds of tobaccos were analyzed by capillary gas chromatography (GC). Volatile flavour compounds were isolated by dichloromethane extraction followed by steam distillation continuous extraction (SDE). In total, 41 volatiles were identified. They consisted mainly of compounds exhibiting aromatic characteristics. The quality and quantity of volatile flavour compounds exhibited different distribution in unloosed or loosed tobaccos. Compared with unloosed tobaccos, volatile flavour compounds showed a decrease after the loosing process.